Numerical simulations of ice crystal icing within a 1.5-stage compressor in an aero-engine - Ping Huang; Xueqin Bu; Guiping Lin; Dongsheng Wen (Case Studies in Thermal Engineering)
Ice crystal icing within aircraft engines at high altitudes significantly impacts safe operation. Due to the complexity of the structure and the thermodynamic conditions, gaining a comprehensive understanding of ice crystal icing presents a considerable challenge. This study establishes a numerical simulation framework to investigate ice crystal icing in compressor structures, taking into account rotational effects and data transfer between blade rows. The simulation framework includes airflow field computation, particle movement model, and icing thermodynamic models. The icing process in a 1.5 stage compressor was simulated, revealing key insights into the ice accretion mechanisms. Results confirm that a certain range of temperature and pressure increases within the compressor causes ice particles to melt and stick to the blade surfaces, ultimately forming ice accretion. Ice accretion is primarily concentrated on the leading edge of the stator blades, with minor accretion on the pressure surfaces. The ice shapes exhibit pronounced three-dimensional characteristics in the spanwise direction due to centrifugal forces. Parameter influence analysis of the ice accretion reveals that temperature, particle size, and ice water content significantly affect the icing process. These findings provide valuable insights into the mechanisms of ice crystal icing in aero engines and contribute to the design of anti-icing systems.